The Effect of Hypertension Education Using Video on Compliance Drink Drug Hypertension on Elderly in Sianpar Village, Sihailhail District Balige Toba District - Erita Saragih; Munarni Simatupang (Universitas Muhammadiyah Manado, 2024)
Hypertension is one of the most dangerous health problems worldwide because hypertension is a major risk factor leading to cardiovascular disease. Management of hypertension can be done with pharmacological therapy by complying with medication and non-pharmacological in the form of hypertension education. Hypertension education using video is an effort to increase medication compliance in the elderly because video media involves two senses, namely sight and hearing, so that it can maximize the information received. The purpose of this study was to see the effect of hypertension education using video on medication compliance in the elderly in Sianipar Sihailhail Village, Balige District, Toba Regency in 2024. This study used a quasi experiment with a pre-post test with a control group. The sample of this study used a simple random sampling technique with a sample size of 42 respondents. The data collection method used the Morisky Medication Adherence scale (MMAS-8) questionnaire and data analysis in this study used the paired T test. The results of the study showed that the average compliance before education in the intervention group was 2.0952 after education became 3.1429, while the average in the control group before education was 2.3810 after education became 3.3333. In the marginal homogeneity test, the Asymp.Sig value was found. (2-tailed) or p value = 0.003 ≤ 0.05. The conclusion of the results of this study is that there is an effect of hypertension education using videos on compliance with taking hypertension medication in the elderly in Sianpar Sihailhail Village, Balige District, Toba Regency, it is recommended that elderly people with hypertension in Sianpar Sihailhail Village, Balige District, Toba Regency in 2019 be given hypertension education using videos to improve compliance with taking hypertension medication.